The Influence of Board Effort, CEO Narcissism, and Real Earnings Management on Audit Report Readability: An Empirical Study of Healthcare Companies Listed on the Indonesia Stock Exchange in 2020-2022 - Lucky Mangapul Simbolon; Pirmansyah Pirmansyah (Inspire Global Insight Journal, 2026)
Purpose of the study: Audit report readability has emerged as a critical factor in financial communication effectiveness, particularly in the healthcare sector where stakeholder decisions carry significant societal implications. The complexity of audit reports can impede stakeholder understanding and decision-making processes. This study examines the influence of board effort, CEO narcissism, and real earnings management on audit report readability in Indonesian healthcare companies. The research aims to understand how corporate governance mechanisms and managerial characteristics affect the clarity and accessibility of financial reporting communications. Materials and methods: The study employs a quantitative approach analyzing 156 firm-year observations from 52 healthcare companies listed on the Indonesia Stock Exchange (IDX) from 2020-2022. Board effort is measured using board meeting frequency and director expertise diversity. CEO narcissism is assessed through compensation relative to other executives and media visibility metrics. Real earnings management is evaluated using the Roychowdhury (2006) model. Audit report readability is measured using the Flesch Reading Ease Score and Fog Index. Multiple regression analysis with robust standard errors is employed to test the hypotheses. Results: The findings reveal that higher board effort significantly improves audit report readability (β = 0.312, p < 0.01), while CEO narcissism negatively impacts readability (β = -0.287, p < 0.05). Real earnings management shows a significant negative association with audit report readability (β = -0.341, p < 0.01). The model explains 43.7% of the variance in audit report readability. Additional analyses confirm the robustness of these relationships across different sub-periods and alternative measurements. Conclusions: Board effort enhances audit report clarity through improved oversight and communication standards, while CEO narcissism and real earnings management practices deteriorate report readability. These findings suggest that effective corporate governance mechanisms are essential for transparent financial reporting in the healthcare sector.